Förebyggande djuromvårdnad mot post-anestetisk myopati hos häst - Rydström, Hanna (2014)
Post-anaesthetic myopathy (PAM) is a serious occasional complication of general anaesthesia in horses. It causes not only pain and suffering to the horse, but also suffering (trauma) to the owner with increased veterinary costs. In the worst case PAM can be fatal. The anaesthetic nurse must know which parameters have to be taken into consideration in the prevention of PAM, to be able to prevent it, and use that knowledge for the animals safety. The aim of this literature review was to investigate and make a presentation of the factors and measurements associated with PAM, with focus on how to monitor these measurements to prevent it from happening, and the advice a Veterinary nurse can give to the horse owner regarding this condition.